Constructs of Meaning and Religious Transformation Current Issues in the Psychology of Religion - Westerink, Herman (Religion and Transformation in Contemporary European Society, 2013)
One of the major trends in the psychology of religion is the growing interest in religious and spiritual meaning making in relation to religious and spiritual transformation processes, notably as the aftermath of traumatic experiences and in situations of crisis, stress or disease when personal well-being is at stake and coping activities and skills are enhanced. This volume covers this broad and complex area of interrelated issues. The contributions focus on religious and spiritual meaning making and transformation. They do not compose an integrated perspective on religious meaning making and transformation processes. Rather, this volume assembles and presents the current state of research on this complex of issues. Thus it not only provides an excellent overview of the psychological study of constructs of meaning and religious transformation, but also contributes to our knowledge of contemporary religious life in the context of socio-cultural transformation processes.